Short Communication: The effects of SO2 and NO2 fumigation on the chlorophyll of Parmotrema perlatum from Mt. Lawu, Cemoro Sewu, Indonesia - EFRI ROZIATY; SUTARNO SUTARNO; SUNTORO SUNTORO; SUGIYARTO SUGIYARTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Roziaty E, Sutarno, Suntoro, Sugiyarto. 2023. Short Communication: The effects of SO2 and NO2 fumigation on the chlorophyll of Parmotrema perlatum from Mt. Lawu, Cemoro Sewu, Indonesia. Biodiversitas 24: 2630-2637. Lichens are symbiotic organisms composed of algae and fungi. Lichens have long been recognized as bioindicators of environmental health. One of the lichen parts that will be affected by pollution is chlorophyll. The lichen thallus was fumigated with the gases from motor vehicle emissions. The lichens under study were Parmotrema perlatum (Huds.) M. Choisy, found in Cemoro Sewu Forest, Magetan, East Java. The categorization of vehicle emission exposure levels includes Level 0 (no fumigation, control group), Level 1 (1.5 hours), Level 2 (3 hours), Level 3 (4.5 hours), Level 4 (6 hours), Level 5 (7.5 hours) and Level 6 (9 hours). The fumigated thallus had already been examined with spectrophotometry. Sulfuric dioxide (SO2) was measured at 324 nm and 328 nm, whereas nitrogen dioxide and chlorophyll were measured at 645 nm and 663 nm. Each test was replicated three times (R1, R2, and R3). Level 6 had the highest NO2 and SO2 content. The highest NO2 content on thallus lichens was 4.00 at Level 6, while the lowest was 2.14 at Level 0 (Control). The highest SO2 content was 1.856 at Level 6, whereas the lowest was 0.231 at Level 0 (Control). The highest chlorophyll content of Parmotrema was found at Level 0, while the lowest was identified at Level 6 (0.245 µg ml-1). The highest content of chlorophyll b was 0.659 (Level 4), while the lowest was Level 6 (0.413 µg ml-1). The thallus Parmotrema responded positively to NO2 and SO2 exposure. Correlation tests between the four components, specifically fumigation, NO2, SO2, and chlorophyll, show a positive correlation between pollutants and chlorophyll.